Global energy networks: Geographies of mergers and acquisitions of worldwide oil companies - Guo, Yue; Yang, Yu; Wang, Chang (Renewable & sustainable energy reviews, 2021)
The global energy merger and acquisition (M&A) network plays an important part in understanding worldwide oil companies and energy flows. Based on data for 26,705 M&As from 1997 to 2018, this paper establishes a global oil and gas M&A network, and conducts statistical and network analysis on the global oil and gas M&A behaviour of countries, industrial chains, and major companies from a geographical perspective. This paper finds as follows. (1) Oil and gas M&As follow the geographical proximity principle. Domestic M&As are the main form of global oil and gas M&As; cross-border M&As account for only a small proportion. (2) Europe and North America are the most active regions in oil and gas cross-border M&As. The most proactive participants include the United States and Canada in North America, as well as the United Kingdom, Netherlands, France, Switzerland, and Russia in Europe. Also, in Asia, such countries as China, India, and Singapore are active participants in global M&As, while some oil-producing countries in Africa and the Middle East are on the verge of M&A networks. (3) The acquisition of international oil companies (IOCs) is significantly more frequent than that of national oil companies (NOCs). NOCs’ global expansion and power to control global oil are far less than that of IOCs. Furthermore, the target areas for NOCs are highly limited. The aim of NOC M&As is to obtain natural resources, and thus, this type of M&A is more subject to other countries’ geopolitical considerations. •This paper analyses oil and gas mergers and acquisitions (M&As) from a geography viewpoint.•The use of network analysis deepens understanding of global oil companies’ M&As.•This paper finds that domestic M&As are the main form of global oil and gas M&As.•Europe and North America are most active in oil and gas cross-border M&As.•NOCs’ global expansion and power to control global oil are far less than that of IOCs.